Faktor Risiko Lingkungan Rumah terhadap Keberadaan Jentik Nyamuk di Lubuk Linggau Timur I - Veni Lara Santi; Yustini Ardillah (Jurnal Kesehatan Komunitas, 2021)
Background: The existence of Aedes sp. is an indicator of the presence of a population of Aedes sp. environmental conditions also greatly affect the incidence of dengue disease, it is also related to the presence of larvae. Citra Medika Health center’s working area is a contributor of Dengue Hemorrhagic Fever (DHF) incidence with increased DHF cased from 2016-2018. Objective: to analyze the relationship between environmental conditions and the presence of Aedes sp. in the Citra Medika Health Center, Lubuk Linggau Timur District 1 in 2020. Methods: It was quantitative research with a cross-sectional design approach. The total sample was 91 respondents, who have met predetermined criteria using the purposive sampling technique, with inclusion criteria and exclusion criteria. The data used in this study are secondary data from Citra Medika Health Center and primary data obtained from interviews and direct observation. Result: It showed that there was a relationship between the implementation of Mosquito Breeding Eradication (p-value 0,047) and the presence of solid waste (p-value 0.039) with the presence of Aedes sp. larvae. Conclusion: This study concludes that the presence of Aedes sp. larvae are caused by factors such as the implementation of Mosquito breeding Eradication DBD and the presence of solid waste.